Estimação Bayesiana do tamanho de uma população de diabéticos através de listas de pacientes - Missiagia, Juliano Gallina (2005)
In this work, a bayesian methodology is shown to estimate the size of a diabethic-su¤ering population through lists containing information data of patients. The applied methodology is analogous of capture-recaptures in animal population. We assume correct the registers of relative information to the patients as well as we take in account correct and incorrect registers of the information. In case the supposed registers are correct, the methodology is developed for two or more lists and the Bayes estimate is determined for the size of a population. In a second model, the occurrency of correct and incorrect registers are considered, presenting a two-stage estimation method for the model parameters using two lists. For both models there are results with simulated and real examples.